Caregiver involvement in psychiatric inpatient treatment – a representative survey among triads of patients, caregivers and hospital psychiatrists. (2020) - Schuster, F.; Holzhüter, F.; Heres, S.; Hamann, J.
Abstract: Aims: Studies on the frequency of caregiver involvement in representative inpatient samples are scarce. The aim of our study was to conduct a representative survey on caregiver involvement in routine inpatient care involving all three parties (patients, caregivers, psychiatrists). Therefore, we performed face-to-face interviews consisting of open-ended questions to gain a deeper understanding of when and how caregivers are involved in care treatment and to identify which topics are mainly discussed. Methods: This cross-sectional survey included inpatients from 55 acute psychiatric wards across ten psychiatric hospitals, their treating psychiatrists and, when possible, their caregivers. In total, we performed semi-structured face-to-face interviews with 247 patients, their treating psychiatrists and 94 informal caregivers. Each psychiatrist named the next two to three patients to be discharged. After a patient had given informed consent, the interview was performed by a researcher. In addition, the psychiatrist and, when possible, the primary caregiver identified by the patient, were also interviewed. Results: It was perceived by both patients and psychiatrists that contact between caregiver and psychiatrist had taken place in one-third of the patient cases. Predictors for psychiatrist-caregiver-contact were revealed in the patient's diagnosis (schizophrenia), a lower history of inpatient stays, and the respective hospital. According to psychiatrists the most frequent subjects of discussion with caregivers involved therapeutic issues and organisational and social-psychiatric topics (e.g. work, living and social support). Patients and caregivers stated that psychiatric treatment and the diagnostic classification of the mental illness were the most frequent topics of conversation. For all three groups, the most often cited reason for missed caregiver involvement was the subjective perception that a caregiver was not in fact needed. Conclusions: Whether or not caregivers were contacted and involved during an inpatient stay strongly depended on the individual hospital. The frequency of involvement of caregivers can certainly be increased by changing processes and structures in hospitals. All three parties (patients, caregivers and psychiatrists) most often stated that the caregiver was not involved in the treatment because they thought it was unnecessary. Evidence demonstrates the positive effect of caregivers' involvement on the therapeutic process but also on the well-being of the caregiver, therefore it is necessary to increase awareness of this evidence among all three interest groups.